2020
DOI: 10.1002/lary.28742
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Magnetic Resonance Imaging of Salivary Glands With Magnetic Resonance Sialography in Sjögren's Syndrome

Abstract: Objectives/Hypothesis To compare the results of magnetic resonance imaging with magnetic resonance sialography (MRSIAL) and the clinical and laboratory characteristics in a well‐characterized cohort of patients with primary or secondary Sjögren's syndrome (SS) meeting the American–European Consensus Group criteria. Study Design: Retrospective, observational, monocentric study. Methods Thirty‐six patients (81% female, mean age = 48 ± 35 years) with primary or secondary SS who underwent MRSIAL were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…24 André et al recently showed that ductal ectasia/stenosis was mainly seen in the PGs, and this "leafless fruit-laden tree aspects (apple-tree appearance)" was correlated with anti-SSA-positivity, with high sensitivity (97%). 4 They also found that fatty infiltration with "pepper-and-salt aspects" and globular atrophy in SMGs were seen in advanced SS cases. Kojima et al also showed that multiple high-signal-intensity spots showed high diagnostic performance for SS, particularly with 100% specificity in SMGs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…24 André et al recently showed that ductal ectasia/stenosis was mainly seen in the PGs, and this "leafless fruit-laden tree aspects (apple-tree appearance)" was correlated with anti-SSA-positivity, with high sensitivity (97%). 4 They also found that fatty infiltration with "pepper-and-salt aspects" and globular atrophy in SMGs were seen in advanced SS cases. Kojima et al also showed that multiple high-signal-intensity spots showed high diagnostic performance for SS, particularly with 100% specificity in SMGs.…”
Section: Discussionmentioning
confidence: 95%
“…26 We could not observe the correlations of MR geographic findings with lymphocyte infiltration in the MSGB results, possibly due to technical issues depending on the sample quality and the limited number of samples. 4 The correlations of immune reactions in salivary glands with structural alterations and glandular degeneration remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR sialography revealed that sialectasis in PG ducts and fat deposition in SMGs were the characteristic features of the SS sicca group. Apple tree-like appearance resulting from sialectactic structural changes was often observed in the PG ducts ( 40 ). Consistently, the microbiome composition was significantly correlated with the radiological findings of the SS sicca group.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of the parotid gland represents the most widely used method in assessing parenchymal changes, clinical activity [ 7 ], and the response to therapy [ 8 ]. Magnetic resonance imaging (MRI) is also used in evaluating patients with pSS; MRI sialography represents the gold standard imaging technique in staging the disease [ 9 ]. The imaging aspect of the parotid and submandibular glands consists of diffuse parenchymal changes, with progressive acinar atrophy and the presence of multiple cystic areas that correspond to the ectasia of the salivary ducts.…”
Section: Introductionmentioning
confidence: 99%